2001
DOI: 10.1111/j.1349-7006.2001.tb01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Expression and Chromosome Mapping of MLZE, a Novel Gene Which Is Preferentially Expressed in Metastatic Melanoma Cells

Abstract: We isolated a novel gene, termed MLZE, from a B16‐BL6 cDNA library after subtraction of B16‐F10 mRNA. Expression levels of mouse MLZE (mMLZE) increased in accordance with metastatic ability of B16 melanoma sublines. Human homolog of mMlze (hMlze) contained one leucine zipper structure and two potential nuclear localizing signals. Northern blot analysis of multiple human tissues showed that hMLZE was expressed primarily in trachea and spleen. We mapped the hMLZE gene (by fluorescence in situ hybridization) to 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 25 publications
0
89
0
1
Order By: Relevance
“…Among the most highly significant genes elevated by WNT3A (Fig. 4B) are Axin2 (35) and Tcf7 (37), which are direct targets of Wnt/ß-catenin signaling; Mme and Mlze, down-regulated genes previously linked to melanoma progression (38,39); Mitf, which is linked to pigment cell fate; and Trpm1, Met, Sox9, and Kit, which are highly expressed during melanocyte and neural crest development (40). The complete list of significantly regulated genes is presented in Dataset S1.…”
Section: Activation Of Wnt/ß-catenin Signaling Is Correlated With Decmentioning
confidence: 99%
“…Among the most highly significant genes elevated by WNT3A (Fig. 4B) are Axin2 (35) and Tcf7 (37), which are direct targets of Wnt/ß-catenin signaling; Mme and Mlze, down-regulated genes previously linked to melanoma progression (38,39); Mitf, which is linked to pigment cell fate; and Trpm1, Met, Sox9, and Kit, which are highly expressed during melanocyte and neural crest development (40). The complete list of significantly regulated genes is presented in Dataset S1.…”
Section: Activation Of Wnt/ß-catenin Signaling Is Correlated With Decmentioning
confidence: 99%
“…Based on the differential protein expressions in gastric and esophageal cancers, human GSDMA, GSDMC, and GSDMD are considered tumor suppressors whereas an overexpression of GSDMB in gastric, uterine cervix, and breast cancers was accompanied by tumor progression and metastasis (3)(4)(5)(6)(7)(8). The overexpression of GSDMC in metastatic melanoma cells is an exception to its apoptotic role (9). In addition to cancer, genome-wide association studies (GWAS) have revealed a correlation between single nucleotide polymorphisms (SNPs) in both the protein coding and transcriptional regulatory regions of the neighboring genes GSDMA, GSDMB, and ORDML3 in the 17q12.2.1 loci and susceptibility to diseases such as asthma (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), type 1 diabetes (21,22), Crohn's disease, ulcerative colitis (22,23), and rheumatoid arteritis (22,24).…”
mentioning
confidence: 99%
“…Members of the protein family that share motifs with DFNA5 that are described in the literature are cancerassociated (Saeki et al, 2000;Thompson and Weigel, 1998;Lage et al, 2001;Watabe et al, 2001) (see http://www.sanger.ac.uk/cgi-bin/Pfam/getacc?PF04598 for DFNA5 family). This is particularly compelling because high levels of HA are a prognostic indicator for malignancy in clinical cases of human breast, ovarian and colon carcinomas.…”
Section: The Role Of Ha In the Developing Earmentioning
confidence: 99%